Stimulus for Teacher's Reading Interest in Improving Teaching Performance and Competence - Norhayati, (Jurnal Serambi Ilmu, 2024)
This study aims to determine how efforts to increase interest in reading and teacher stimulus to competence. teaching at SD Negeri Rokan Hilir Riau teachers. The research subjects were all 8 teachers of the State Elementary School 004 Bukit Damar, Simpang Kanan District, Rokan Hilir Regency. Data collection methods are observation techniques and interview techniques. The data processing technique uses a qualitative research approach and the percentage formula. The results of the research show that the development of the program for organizing the love of reading educational reference books in the library can improve the competence of teacher performance in teaching and learning activities and teachers gain new experience in the implementation of the implementation of the learning implementation plan.